Locating inclusion within the OECD's assessment of global competence: An inclusive future through PISA 2018?. Issue 1 (January 2022) - Cobb, Donella; Couch, Daniel
In 2018, Programme for International Student Assessment (PISA) introduced an assessment of global competence to equip young people with the skills, knowledge, attitudes and values to create "an inclusive and sustainable world" (OECD, 2018 : 1). Throughout this article, we take the OECD seriously at their claims around inclusion. We look critically at the global competence framework to ask what PISA means by inclusion and trouble the idea that inclusion can function effectively within a global standardized assessment. We put Bernstein's (2000 ) notion of recontextualization to work to demonstrate how inclusion takes on new meaning as it moves between each iteration of the global competence framework. We show how this recontextualization re-orientates inclusion from a social justice imperative toward supporting young people's inclusion into a globalized market economy.